The Complete Works of Gabrio Piola: Volume II Commented English Translation - dell'Isola, Francesco; Andreaus, Ugo.; Cazzani, Antonio; Esposito, Raffaele; Placidi, Luca.; Perego, Umberto; Maier, Giulio; Seppecher, Pierre; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the second volume of Piola's original Italian text together with the English-language translation and comments, showing convincingly that Gabrio Piola's work must still be regarded as a modern theory. Gabrio Piola's work has had an enormous impact on the development of applied mathematics and continuum mechanics. As such, a committee of scientific experts took it upon themselves to translate his complete works. In a second step, they commented on Piola's work and compared it to modern theories in mechanics in order to stress Piola's impact on modern science and prove and confirm that he achieved significant milestones in applied mathematics.
Sull'applicazione de' principj della Meccanica Analitica del Lagrange ai principali problemi -- Sulla teorica del pendolo -- Sulla teorica delle funzioni discontinue -- Sull'applicazione del calcolo delle probabilità alle scienze morali -- Da quali cause fisiche Newton ha derivati i moti dei corpi mondani -- Esposizione del moderno sistema atomistico -- I Principj della Meccanica Razionale dedotti dalle nostre prime cognizioni, sviluppati secondo il metodo analitico, appoggiati al solo calcolo delle funzioni -- Principio filosofico per la misura delle quantità continue variabili -- Riflessioni da farsi da chi segua in analisi la metafisica Lagrangiana quando prende a studiare la fisica molleculare -- Riflessioni sulle unità e sulle misure delle varie quantità concrete.
Keywords: Mechanics, Applied; Solids; Mathematical physics; Physics -- Philosophy; Solid Mechanics; Mathematical Physics; Philosophical Foundations of Physics and Astronomy